Counter-Narratives of Structural Oppressions, Stigma and Resistance, and Reproductive and Sexual Health Among Youth Experiencing Homelessness. (August 2022) - Henriques, Emilia; Schmidt, Catherine; Pascoe, Rachael; Liss, Kira; Begun, Stephanie
Youth experiencing homelessness (YEH) face myriad injustices regarding their reproductive and sexual health and rights. Reproductive and sexual health research with YEH often explores condom-use and sexually transmitted infections, potentially contributing to narrow conceptualizations of YEH as "unclean" or in need of disease-screening. A narrative theory perspective was applied to this study, which allowed for the emergence of alternative storylines, or counter-narratives, which attend to manifestations of power and oppression within the lives of marginalized individuals. Qualitative interviews engaged 30 young people (ages 18–21) accessing shelter services. Narrative analyses identified YEHs' documentations of dominant narratives related to structural oppressions, stigma, and numerous dimensions of reproductive and sexual health including how they create, through their resistance, counter-narratives that include their preferred futures. YEH emphasized systemic sources of stigma and outlined their criticisms of the state. Within-group stigma emerged as a noteworthy theme, with YEH showing both empathy and ambivalence towards other YEH, along with internalization of stigmatizing narratives about pregnancy and homelessness. Approaches to service provision that further amplify youths' voices in naming and challenging the many oppressions and stigmas they face should be prioritized. Moreover, policies should be implemented to dismantle the actual root causes of challenges faced by YEH, rather than perpetuating them through measures rooted in interlocking oppressions of discrimination, inequity, and judgment.